1987
DOI: 10.3406/paleo.1987.4427
|View full text |Cite
|
Sign up to set email alerts
|

The Dalma Tradition : Prehistoric Inter-Regional Cultural Integration in Highland Western Iran

Abstract: In the mid-fifth millennium B.C., the remarkably homogeneous Dalma ceramic assemblage spread throughout much of the rugged Zagros highlands of north and central western Iran. This study examines Dalma pottery production and distribution patterns by utilizing two distinct kinds of evidence. First, the several diagnostic Dalma wares and their geographical distributions are presented. Second, stylistic and apparent (macroscopic) ware homogeneity is investigated by instrumental neutron activation analysis (INAA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 1 publication
1
9
0
1
Order By: Relevance
“…During the MC period various types of wares represent developments in pottery productions and also communications with the adjacent regions. The reports concerning presence of IDW types even in Azerbaijan region verifies this fact of interactions (Hamlin, 1975;Henrickson & Vidali, 1987). Archaeological evidences from CZM, show two distinct economic strategies taking place in the MC period.…”
Section: The Settlement Pattern and Distribution Of Ware Types In Thesupporting
confidence: 58%
“…During the MC period various types of wares represent developments in pottery productions and also communications with the adjacent regions. The reports concerning presence of IDW types even in Azerbaijan region verifies this fact of interactions (Hamlin, 1975;Henrickson & Vidali, 1987). Archaeological evidences from CZM, show two distinct economic strategies taking place in the MC period.…”
Section: The Settlement Pattern and Distribution Of Ware Types In Thesupporting
confidence: 58%
“…Henrickson and Vitali have previously advanced a similar view on the similarities in distribution of cultural material in assemblages from the fifth millennium B.C. Zagros and northwestern Iran (Henrickson and Vitali 1987). While similar views have also been espoused for cultural relations of eighth and seventh millennium B.C.…”
Section: Discussionmentioning
confidence: 83%
“…A similar conclusion can be drawn from the survey results in the region. Provenance analysis has also shown that all Dalma ceramics were produced locally (Vitali, Henrickson 1987;Tonoike 2009 (Achundov 2007;Müseyi-bli 2007;Lyonnet 2007b;Lyonnet et al 2008;2012;Marro 2010;2012;Helwing 2012), Eastern Anatolia (Frangipane 2012) and Northern Mesopotamia (Stient 2012) enable scholars to define the chronological range of the Chalcolithic and build up a solid internal periodisation and properly articulated timeline for regional developments in this phase (Marro 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Dalma is an unusual ceramic phenomenon for this time range: a widespread, but technically and stylistically homogeneous material cultural tradition, at home in a topographically severe highland region. The Dalma period is particu-larly interesting because of the extremely large geographic spread of its ceramics, ranging from the 'widely separated mountain plains such as the (Dyson 1962;Hamlin 1975;Henrickson, Vitali 1987;Hole 1987;Levine, Young 1987;Solecki, Solecki 1973;Vandiver 1985;Voigt, Dyson 1992;Young, Levine 1974;Pecorella, Salvini 1984;Kroll 1984;1994;Tonoike 2009;Vitali, Henrickson 1987;Hamlin 1975;Hole 1987b;Oates 1983.261;Voigt, Dyson 1992). Recently, scholars have suggested a combination of factors, such as trade and exchange, the movement of material goods and information, migration, diffusion, and local emulations of foreign styles to explain Dalma cultural phenomena (Voigt 1983;Tonoike 2009).…”
Section: Dalma Period In Nw Iran (5000-4500 Bc)mentioning
confidence: 99%